CHISEL: An optical slice of the wide-area network - Kumar, Abhishek Vijaya; Owens, Bill; Bjørner, Nikolaj; Yin, Yawei; Guan, Binbin; Bahl, Victor; Singh, Rachee (NSDI, 2024)
Network slicing reserves a portion of the physical resources of radio access networks and makes them available to consumers. Slices guarantee traffic isolation, strict bandwidth and quality of service. However, the abstraction of slicing has been limited to access networks. We develop CHISEL, a system that dynamically carves slices of the wide-area network (WAN), enabling an end-to-end network slicing abstraction. CHISEL creates optical slices between WAN endpoints to avoid queueing and congestion delays inherent in packet switched paths in WANs. CHISEL incrementally allocates optical spectrum on long-haul fiber to provision slices. This task is made challenging by the co-existence of data-carrying channels on the fiber and numerous physical constraints associated with provisioning optical paths e.g., spectrum contiguity, continuity and optical reach constraints. CHISEL leverages the empirical finding that cloud WANs have abundant optical spectrum to spare — 75% of optical spectrum on 75% of fiber spans is unused. CHISEL can optimally allocate terabits of slice requests while consuming minimal optical spectrum within seconds without increasing spectral fragmentation on fiber. CHISEL trades-off optimality of slice bandwidth allocation for faster run-time, provisioning slices within 2% of optimal in less than 30 seconds in a commercial cloud WAN. Finally, CHISEL reduces the latency of provisioning optical slices on hardware by 10X. Compared to IP tunnels of equivalent capacity, CHISEL consumes 3.3X fewer router ports.